2017
DOI: 10.2169/internalmedicine.56.8545
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Hypocalcemia Developed in Gastric Cancer Accompanied by Osteoblastic Metastasis

Abstract: Paraneoplastic syndromes are generally defined as clinical disorders associated with malignant diseases, and hypocalcemia associated with cancer is a rare condition. A woman in her 60s was referred to our hospital for the further examination of massive ascites due to carcinoma of unknown primary origin. She complained of numbness around her lips, and marked hypocalcemia of 5.0 mg/dL was noted. After two courses of chemotherapy, computed tomography showed a decrease in the ascites, and her serum calcium level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Typically, metastatic bone lesions with osteoblastic changes from gastric cancer are rare, with fewer than 20 cases having been reported to date [7]. A review of gastric cancers by Okazaki et al [8] identified that up to 80% of patients have poorly differentiated gastric cancers (signet ring cell carcinomas or poorly differentiated adenocarcinomas) [7]. The specific symptoms of osteoblastic metastasis of gastric cancers are hypocalcemia (in 28% of the cases) and elevated ALP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, metastatic bone lesions with osteoblastic changes from gastric cancer are rare, with fewer than 20 cases having been reported to date [7]. A review of gastric cancers by Okazaki et al [8] identified that up to 80% of patients have poorly differentiated gastric cancers (signet ring cell carcinomas or poorly differentiated adenocarcinomas) [7]. The specific symptoms of osteoblastic metastasis of gastric cancers are hypocalcemia (in 28% of the cases) and elevated ALP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid proliferation of osteoclasts via expression of receptor activator of nuclear factor kappa-B ligand (RANKL) in gastric cancer cells plays an important role in the development of DC [10,11]. In addition, factors such as insulin-like growth factor (IGF), transforming growth factor-beta (TGF-β), bone morphogenetic protein (BMP), and platelet-derived growth factor (PDGF) play an important role in the development of cancer with the activation of osteoblastic lesions [7,9,12]. This process is different from the vicious cycle of osteolytic metastasis; it promotes the differentiation and function of osteoclasts and reduces osteoblast function [13].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 3 ] It has been reported in gastric and salivary carcinoma but not in bladder cancer. [ 4 , 5 ] Skeleton is one of the most frequent sites of metastasis after lung and liver [ 26 ] and the relative incidence of bone metastasis in bladder cancer is 40%. [ 6 ] Bone metastases increase the risks of morbidity and SREs such as hypercalcemia, bone pain, pathological fractures, cord compression, and bone marrow dysfunction and patients with bladder cancer and bone metastases generally have poorer prognosis with a median survival of 6 to 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblastic bone metastasis contributing to hypocalcaemia is typically described in prostate and breast cancer [ 2 , 3 ] and rarely in gastric and salivary carcinoma. [ 4 , 5 ] To date, hypocalcaemia resulting from osteoblastic bone metastases in bladder cancer has not been reported. Bone is a common site of metastasis and can occur in 40% of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This alteration is believed to be secondary to the production of parathyroid hormone-related protein (PTH) by neoplastic cells (BERGMAN, 2012;MIRRAKHIMOV, 2015). Hypocalcaemia was related to the likely occurrence of hypomagnesemia, vitamin D deficiency, massive cell lysis, osteoblastic metastasis, or low levels of PTH (FAROLFI et al 2015;OKAZAKI et al, 2017).…”
Section: Case Reportmentioning
confidence: 99%